The development and pilot testing of a doctor-pharmacist collaboration intervention to improve medication safety for patients with chronic disease in primary care / Renukha a/p Selllapans - Selllapans, Renukha (2017)
Patients with chronic diseases are often prescribed with complex medication regimens. This puts them at a higher risk of adverse drug events, leading to poor disease control and increased health care costs. Previous studies have shown that the provision of pharmaceutical care by pharmacists as part of a multidisciplinary team, can improve disease control and medication safety. It is however unclear how these interventions were developed, and how the doctor-pharmacist working relationship affects patients’ therapeutic outcomes. The aim of this study was to systematically develop and pilot test a doctor-pharmacist collaboration intervention to improve medication safety for patients with chronic diseases in primary care. This study was divided into 3 phases. In phase 1, qualitative interviews were conducted with primary care physicians (PCPs), pharmacists, and patients at a teaching hospital in Malaysia. These interviews aimed to explore the problems encountered by PCPs when prescribing, by pharmacists while dispensing, and by patients when using medications for chronic diseases. In phase 2, an intervention called the “Physician-Pharmacist Partnership for Patient Safety (4Ps)” was developed based on findings from phase 1, literature and conceptual framework. This intervention was reiteratively reviewed by a steering committee, and tested for feasibility and acceptability. The 4Ps consisted of briefings to the PCPs and pharmacists, identification of patients with potential drug related problems (DRPs) by the PCP, pharmacist’s assessment of patients for DRPs, discussion between the PCP and pharmacist regarding the DRPs identified, feedback by the PCP to the pharmacist on patients’ medication plan after the doctor-patient consultation, and medication dispensing and counselling by the pharmacist. To assess the level of doctor-pharmacist collaborative working relationship, two instruments, the Physician-Pharmacist Collaborative Index (PPCI) for physicians, and the PPCI for pharmacists, were validated. Phase 3 was a pilot test of the 4Ps. Four PCP-pharmacist pairs provided this intervention once a week over three weeks. In addition to the PPCI, qualitative interviews were conducted with the PCPs and pharmacists to explore their experiences in establishing a collaborative working relationship with each other. The DRPs identified and resolved by the PCP-pharmacist pairs were also recorded. Findings from Phase 1 highlighted the need to support PCPs’ medication-prescribing practice, improve patients’ medication knowledge and medication-taking behavior, create a system to engage pharmacists more actively in patient care, and improve interprofessional communication between PCPs and pharmacists. This led to the development of the 4Ps in phase 2. Both the PPCI for physicians and pharmacists were found to be valid and reliable in assessing doctor-pharmacist collaborative working relationship in Malaysia. Findings from phase 3 provided preliminary evidence that the 4Ps enhanced the collaborative working relationship between PCPs and pharmacists, to identify and resolve patients’ DRPs. The 4Ps was well accepted by PCPs and pharmacists. However, its integration into routine practice will require a change in policy and practice. In conclusion a doctor-pharmacist collaboration intervention was successfully developed based on needs assessment, evidence and theory. More rigorous evaluation is needed to confirm the effectiveness of the intervention in improving patients’ medication safety.